Google Classroom Application Effectiveness in Learning on Learning Activity and Achievement - wikan budi utami; sugeng raharjo; Ponoharjo Ponoharjo (Mathematics Education Journal, 2021)
The purpose of this study is to describe: (1) whether the learning achievement using the google classroom application reach the KKM target beyond 55%. (2) whether the google classroom application can improve student learning achievement. (3) how active students are in using the google classroom application. The data collection methods used were tests, observation, and documentation. The research population was the students of class XI. The research sample was XI IPA 3. The sampling technique was purposive sampling. The results showed that: (1) The learning achievement that were taught using the google classroom application, whose value exceeds the KKM is more than 55%. (2) The learning outcomes of students taught using the google classroom application are better with students who are taught using direct learning. (3) The level of active learning of students using the google classroom application is good.